REGULATION IN THE PERUVIAN CIVIL ORDER OF ELECTRONIC CONTRACTS - Peter Jesus Manzaneda Cabala (2019)
The present work carried out under a general objective of determining the legal arguments to incorporate in the Peruvian civil system in an optimized way the electronic contracts, whose research was carried out under an explanatory methodology, with a mixed approach, with a non-experimental design and of transversal cut , whose data collection technique being direct observation and subtechnics such as interpretation and argumentation, results are reached that most notaries and users do not have enough knowledge in electronic contracts and also mention that this type of trust does not generate contracts, thus concluding, "The legal implications of generating regulation in the civil system, are manifested in: consent as a requirement of electronic contracting, formality as an element of an electronic contract and legal security in electronic contracting"